Impacto del control de los organismos reguladores del turismo en la calidad y sostenibilidad de los emprendimientos turísticos rurales en la parroquia de San Rafael de la laguna provincia de Imbabura 2024. Caso de la asociación de turismo rural “Coraza Ñan' - Rivadeneira Valenzuela, Allizon Sabinne (2025)
The control exercised by tourism regulatory bodies plays an essential role in the quality and sustainability of rural tourism ventures. In this context, the regulation and supervision of entities such as the Ministry of Tourism of Ecuador (MINTUR) are essential to ensure that these projects meet quality standards and environmental and social sustainability. In the parish of San Rafael de la Laguna, province of Imbabura, the Rural Tourism Association 'Coraza Ñan' is a relevant case study that led to having as a general objective of this research to examine how the control and supervision mechanisms implemented by tourism regulatory bodies have affected the quality of service and the sustainability of rural tourism ventures such as the Rural Tourism Association 'Coraza Ñan' in the period 2024. Having as a methodological basis a qualitative approach, a descriptive level of depth, with scientific methods such as the normative, the socio-legal and the synthetic analytical, which through documentary review and interviews as techniques allowed to identify opportunities for improvement that strengthen the tourist offer and the promotion of sustainable development in the parish of San Rafael de la Laguna. Among the main results obtained, an insufficient participation of entities such as the Ministry of Tourism of Ecuador (MINTUR) and the Ministry of Environment, Water and Ecological Transition in the supervision and regulation of these projects was evident. In the parish of San Rafael de la Laguna, province of Imbabura, the Rural Tourism Association 'Coraza Ñan' envisions this challenge. In the short and medium term, the lack of effective intervention could have serious environmental consequences, including high levels of pollution in Lake San Pablo, the largest lake in Ecuador.